2021
DOI: 10.1387/theoria.21967
|View full text |Cite
|
Sign up to set email alerts
|

Learning from scientific disagreement

Abstract: The article addresses the question of how should scientific peers revise their beliefs (if at all) upon recognized disagreement. After presenting the basics of peer disagreement in sections 1 and 2, we focus, in section 3, on a concrete case of scientific disagreement, to wit, the dispute over the evidential status of randomized control trials in medical practice. The examination of this case motivates the idea that some scientific disagreements permit a steadfast reaction. In section 4, we support this conclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Similarly, whether HOE should play the role of defeater in scientific disagreements has also been a contested issue (see, e.g., Straßer et al 2015; Borge and Guercio 2021). Our aim in this section is not to argue in favor of a specific weight of HOE relative to the weight of FOE.…”
Section: The Role Of Hoementioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, whether HOE should play the role of defeater in scientific disagreements has also been a contested issue (see, e.g., Straßer et al 2015; Borge and Guercio 2021). Our aim in this section is not to argue in favor of a specific weight of HOE relative to the weight of FOE.…”
Section: The Role Of Hoementioning
confidence: 99%
“…Whereas some have argued that disagreeing peers need to conciliate (Elga 2007;Christensen 2010;Feldman 2006Feldman , 2007, others have defended a steadfast approach (Cruz and Smedt 2013;Kelp and Douven 2012;Enoch 2010). Yet others have suggested that different cases and contexts of disagreement may call for different verdicts (Kelly 2010;Konigsberg 2012;Christensen 2010;Douven 2010;Lackey 2013;Worsnip 2014;Borge and Guercio 2021). In addition, the bulk of this literature has focused on disagreements in the standard context of inquiry rather than inquiry in the context of "fast science" to which the current case belongs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation